The effect of antibiotics on cytokine production by mononuclear cells and the cross-talk with colon cancer cells - Meir Djaldetti; Nimrod Nachmias; Hanna Bessler (GarVal Editorial Ltda., 2016)
Context: Antibiotics belong to the powerful weapons applied against microbial infections. It is notable that in addition to their antimicrobial effect they express immunomodulatory and anti-cancer activities. Aims: To explore the effect of four antibiotics on the immune cross-talk between peripheral blood mononuclear cells (PBMC) and colon carcinoma cells from two human lines. Methods: Cefotaxime, meropenem, ampicillin and vancomycin were separately added to PBMC co-incubated with cells from two human colon carcinoma cell lines, i.e. HT-29 and RKO. After 24 hours, the level of the following cytokines produced by PBMC was evaluated: IL-6, IL-1ra, IL-1β, TNFα, IFNγ and IL-10. Results: All four antibiotics did not affect the generation of IL-6 and IL-1ra in both co-cultures. On the other hand all of them restrained the production of IL-1β by PBMC incubated with HT-29 cells. In the same incubation mixture cefotaxime, vancomycin and meropenem decreased IFNγ and IL-10 production, while ampicillin and vancomycin inhibited TNFα. As for PBMC incubated with RKO carcinoma cells, cefotaxime inhibited the production of IL-1β, IFNγ and mildly of IL-10, whereas vancomycin repressed that of IL-1β, TNFα and IFNγ. Notably, vancomycin increased the production of IL-1β and decreased that of TNFα and IFNγ. The results indicate that the four antibiotics examined exert a modulatory effect on the immune cross-talk between PBMC and human colon cancer cells from two lines expressed by a different impact on pro-and anti-inflammatory cytokines generation. Conclusions: These findings support the conception that antibiotics may express not only an anti-microbial effect, but also possess an anti-cancer activity that may be considered for integration to the therapeutic arsenal against cancer.